Harnessing Cattail Biomass for Sustainable Fibers and Engineered Bioproducts: A Review - Mahmuda Parvin; Md Shadhin; Marzia Dulal; Mashiur Rahman (Global Challenges)
Abstract Cattail (Typha), a wetland plant, is emerging as a sustainable materials resource. While most of the Typha species are proven to be a fiber‐yielding crop, Typha latifolia exhibits the broadest leaf size (5–30 mm), yields highest amount of fiber (≈190.9 g), and captures maximum CO2 (≈1270 g). Alkaline retting is the most efficient degumming process for cattail fibers to achieve maximum fiber yield (30%–46%). Cattail leaves exhibit a distinctive bionic structural model consisting of epidermis and leaf blade at macro level and non‐diaphragm aerenchyma, fiber cables, partitions, and diaphragms at micro level. Cattail fibers hold promise to be utilized as a high‐performance composite part and as efficient energy storage devices in clean energy vehicles. The former is attributed to their lower density (≈1.26–1.39 gm/cm3) and higher tensile modulus (≈66.1 GPa after treatment), while the latter is attributed to their porous structure and chemical stability. Therefore, integrating the knowledge of plant biology and materials chemistry is crucial for enhancing fiber characteristics and producing engineered bioproducts. The environmental benefits of cattails, degumming methods, leaf and fiber structures, their properties and applications is reviewed. Finally, it discussed future research directions aimed at developing bioengineered, biodegradable products from it with minimal environmental impact.